Gram-scale synthesis of nitrogen doped graphene quantum dots for sensitive detection of mercury ions and l-cysteine. Issue 57 (16th October 2019) - Mao, Yuang; Zhao, Chang; Ge, Shuyan; Luo, Tao; Chen, Jie; Liu, Jiyang; Xi, Fengna; Liu, Junjie
Abstract : One-step and gram-scale synthesis of nitrogen doped graphene quantum dots is realized for their sensitive detection of Hg 2+ and l -Cys. Abstract : Sensitive and reliable detection of mercury ions (Hg 2+ ) and l -cysteine (l -Cys) is of great significance for toxicology assessment, environmental protection, food analysis and human health. Herein, we present gram-scale synthesis of nitrogen doped graphene quantum dots (N-GQDs) for sensitive detection of Hg 2+ and l -Cys. The N-GQDs are one-step synthesized using bottom-up molecular fusion in a hydrothermal process with gram-scale yield at a single run. N-GQDs exhibit good structural characteristics including uniform size (∼2.1 nm), high crystallinity, and single-layered graphene thickness. Successful doping of N atom enables bright blue fluorescence (absolute photoluminescence quantum yield of 24.8%) and provides unique selectivity towards Hg 2+ . Based on the fluorescence quenching by Hg 2+ (turn-off mode), N-GQDs are able to serve as an effective fluorescent probe for sensitive detection of Hg 2+ with low limit of detection (19 nM). As l -Cys could recover the fluorescence of N-GQDs quenched by Hg 2+, fluorescent detection of l -Cys is also demonstrated using turn-off-on mode.